Adverse birth outcomes among Orang Asli in Kelantan for years 2018-2020 : the proportions and associated maternal factors - Khan, Erwan Ershad Ahmad (2021)
Adverse birth outcomes refer to serious events that occurred to infants accompanying their birth and has the potential to impact their later life as well as the mothers. Adverse birth outcome includes low birth weight, preterm birth, stillbirth, early neonatal death and macrosomia. This secondary data record review study aimed to measure the proportions of adverse birth outcomes and maternal factors associated with low birth weight among Orang Asli infants in Kelantan for years 2018 - 2020. This study utilised data from the birth registry, death registry and antenatal records. Proportionate stratified random sampling was done to select 327 samples from five antenatal centres involved with Orang Asli. Multiple logistic regression analysis was used to determine maternal factors associated with low birth weight among Orang Asli infants. The proportions of adverse birth outcomes were as follows: low birth weight is at 16.2%, preterm birth at 7.3%, stillbirth at 0.6%, early neonatal death at 0.6% and macrosomia at 0.9%. A total of 26.6% of primiparous mothers, 20.8% of mothers with anaemia in pregnancy and 41.7% of mothers with hypertension had low birth weight infants. Maternal factors associated with low birth weight infants include primiparity (AdjOR: 2.88, 95% CI: 1.44, 5.78), anaemia in pregnancy (AdjOR: 2.33, 95% CI: 1.18, 4.61) and hypertension (AdjOR: 4.21 95% CI: 1.23, 14.44). In conclusion, the proportions of adverse birth outcomes especially low birth weight among Orang Asli in Kelantan is higher than the general population and comparable to other indigenous groups from other parts of the world. Explicit preventive measures against low birth weight and its determining factors and the development of practical and focused strategies should be adopted by the stakeholders to reduce the proportions of low birth weight among Orang Asli.